Effect of organic solvent on the cold sintering processing of SrFe12O19 platelet-based permanent magnets. Issue 3 (March 2022) - Serrano, Aida; García-Martín, Eduardo; Granados-Miralles, Cecilia; López-Sánchez, Jesús; Gorni, Giulio; Quesada, Adrián; Fernández, José F.
Abstract: In this work we have investigated the effect of the solvent during the processing of SrFe12 O19 platelet-based permanent magnets by cold sintering process (CSP) plus a post-thermal treatment. Several organic solvents: glacial acetic acid, oleic acid and oleylamine have been analyzed, optimizing the CSP temperatures at 190−270 °C, under pressures of 375−670 MPa and 6−50 wt% of solvent. Modifications in the morphological and structural properties are identified depending on the solvent, which impacts on the magnetic response. Independently of the solvent, the mechanical integrity of ferrite magnets obtained by CSP is improved by a post-annealing at 1100 °C for 2 h, resulting in relative densities around 92 % with an average grain size of 1 μm and a fraction of SrFe12 O19 phase >91 %. HC ≥ 2.1 kOe and MS of 73 emu/g are obtained in the final sintered ceramic magnets, exhibiting the highest HC value of 2.8 kOe for the magnet sintered using glacial acetic acid.